Resistance nothingness: becoming tradition - Суходуб, Т.Д. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
This article analyzes the emergence within the philosophy of "Russian cosmism" concept rejection death NF Fedorov.